2018
DOI: 10.1590/s0034-759020180309
|View full text |Cite
|
Sign up to set email alerts
|

Hawkerpreneurs: Hawkers, Entrepreneurship, and Reinventing Street Food in Singapore

Abstract: The hawker center is an icon of contemporary Singapore and an essential element of national identity, but one that has undergone multiple reinventions. Most recently hawking has repeatedly been presented as approaching crisis, prompted by an aging hawker population. The response of the Singapore government has been to begin another historic transformation of the hawker, focusing on the hawker entrepreneur - the hawkerpreneur. Ahead of reinvention, codification of knowledge about hawking was required and provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 14 publications
4
20
0
Order By: Relevance
“…The hypothesis is supported, successor willingness is significantly related to family succession in the food hawking business of Malaysia. The result is in agreement with the findings of Tarulevicz (2018). The study of Tarulevicz (2018) is more similar to this study as it examines the likelihood of potential family successors in the food hawking business in Singapore; it is therefore similar in terms of the target population.…”
Section: Successor Willingnesssupporting
confidence: 87%
“…The hypothesis is supported, successor willingness is significantly related to family succession in the food hawking business of Malaysia. The result is in agreement with the findings of Tarulevicz (2018). The study of Tarulevicz (2018) is more similar to this study as it examines the likelihood of potential family successors in the food hawking business in Singapore; it is therefore similar in terms of the target population.…”
Section: Successor Willingnesssupporting
confidence: 87%
“…The hypothesis is supported, successor willingness is signi cantly related to family succession in the food hawking business of Malaysia. The result is in agreement with the ndings of Tarulevicz (2018). The study of Tarulevicz (2018) is more similar to this study as it examines the likelihood of potential family successors in the food hawking business in Singapore; it is therefore similar in terms of the target population.…”
Section: Successor Willingnesssupporting
confidence: 86%
“…The result is in agreement with the ndings of Tarulevicz (2018). The study of Tarulevicz (2018) is more similar to this study as it examines the likelihood of potential family successors in the food hawking business in Singapore; it is therefore similar in terms of the target population. The ndings are aligned with the results of this study as Tarulevicz (2018) reported that if successors were willing to succeed the family hawker business, they would do so regardless of their current job and income.…”
Section: Successor Willingnesssupporting
confidence: 86%
See 1 more Smart Citation
“…The major difference street trading has from other informal economic sectors is its propensity of being in every corner of the streets in the city and this makes it worthwhile to investigate and define those characteristics of street trading. Moreover, street hawking remains an integral part of every developing economy and targeted investment in it is expected to contribute to economic development especially when infused with innovation [27].…”
Section: A the Characteristics Of Street Vendorsmentioning
confidence: 99%